PANDANGAN ULAMA DAN MASYARAKAT KECAMATAN SINGKIL KABUPATEN ACEH SINGKIL TENTANG ADAT TEMETOK DALAM WALIMAH AL-‘URSY - ricky irbansyah; Armia Armia; Hasbullah Ja'far (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2021)
Marriage is the initial process of starting a family life, in conducting marriage it is recommended also to carry out Walimah Al-rsUrsy or a wedding reception to inform the public that they are married so that later misunderstanding and slander will not occur. Walimah Al-rsUrsy means bridal food. The point is the food that is provided specifically at weddings. In Singkil Subdistrict, Aceh Singkil Regency in carrying out Walimah Al-'Ursy there is the Temetok custom, where each wedding party or circumcision, a large family will be summoned one by one to surround the bride or circumcision offer, then give a certain amount of money usually from the big family. giving in large quantities. With this custom, there are families who feel burdened. This fact raises the question: What is meant by Temetok adat in Walimah Al-'Ursy in Singkil District? What is the Temetok adat process in Walimah Al-'Ursy in Singkil District? -'Ursy in Singkil District ?. In this study the authors used a descriptive analysis method, which is a study that aims to describe a current reality. The technique used in obtaining data is by using field research as a source, namely by conducting interviews with related parties as well as observing and researching the literature, as secondary data, namely by studying and reading books, books book. As for the results that the authors found in this study and supported by the Qur'an and Al-Hadith and Islamic law, the Ulama are of the opinion that the Temetok customary law in Walimah Al-'Ursy is permissible, if no one feels objected and there is no who demanded to be returned with the custom. But if there are people who feel objected and demanded to be returned with adat, then the law is not in accordance with Islamic law. And this needs to be socialized by the Ulama to the people who are still implementing the Temetok custom.